MV-RLU - Jaeho Kim; Ajit Mathew; Sanidhya Kashyap; Madhava Krishnan Ramanathan; Changwoo Min (Proceedings of the Twenty-Fourth International Conference on Architectural Support for Programming Languages and Operating Systems, 2019)
We report an 80-year-old man with a descending thoracic aortic aneurysm and recent pancreaticoduodenectomy for pancreatic adenocarcinoma. 18F-FDG PET/CT performed for elevated inflammatory markers demonstrated a hypermetabolic hepatic lesion, subsequently diagnosed as a liver abscess, and intense periaortic uptake with new periaortic soft-tissue thickening and aneurysm enlargement compared with prior CT. One month later, CT for chest pain showed further aneurysm enlargement and progressive mural abnormalities, raising suspicion of an infected aneurysm, although inflammatory aneurysm remained a differential diagnosis. This case highlights the potential value of 18F-FDG PET/CT in detecting metabolically active aneurysmal wall disease associated with rapid aneurysm progression.